Agrochemicals and Personal Care Products: Occurrence, Effects, Analytical Determination and Treatment Processes - AYANDA, Olushola Sunday (Review of Environment and Earth Sciences, 2014)
Pollution caused by agrochemicals and personal care products (PCPs) remains a severe problem worldwide. Runoff of agrochemicals from farms leads to contamination of the surface water and groundwater while PCPs are discharged through laundering, washing and bathing. PCPs enter the municipal wastewater treatment plants and are incompletely removed during wastewater treatment. To reduce or eliminate the negative impact of these pollutants to human beings, animals, organisms and the environment, water should be well treated and wastewater should be treated to zero release before discharge into the environment. In this study, the occurrence, toxic effects, analytical determination and treatment processes of agrochemicals and PCPs in water and wastewater will be presented. This review will serve as valuable literature for researchers, policy makers, and environmental pollution consultants. Moreover, it will open the door to significant discussion on agrochemicals and PCPs.